Importancia de los canales de distribución de la empresa Coca Cola. - Medina Jara, Carlos Xavier (My University, 2018)
The distribution channels of the Coca Cola Company have proved to be a fundamental pillar for the company to be among the most successful companies in the world, for that reason the present research project aims to diagnose the distribution channels of the mentioned brand, identifying its characteristics and structure and determining its importance to achieve the success.Accordingly, concepts and research related to the topic were reviewed, besides of the application of an interview and subsequent analysis of the data collected. As a result, it has been determined that Coca Cola Company has different segmented distribution channels, that means that they are specific or adapted according to the characteristics of the environment and the customers; and the importance of the distribution channels is based on the efficiency of the timely delivery of their products to the final consumer, based on a strategic planning of the sales and the distribution process (delivery, transport and storage), since this facilitates the optimization of resources and directly affects the level of income. Therefore, it is concluded that the success of the Coca Cola Company is largely based on its distribution and sales strategy.
Los canales de distribución de la Compañía Coca Cola han resultado un puntal fundamental para que se sitúe entre las empresas más exitosas a nivel mundial, es por eso que el presente trabajo de investigación plantea como objetivo el diagnóstico de los canales de distribución de esta marca, identificando sus características y estructura y determinando su importancia para lograr el éxito alcanzado. En consecuencia, se revisaron conceptos e investigaciones relacionadas al tema, además de la aplicación de una entrevista y posterior análisis de los datos recopilados. Como resultado se determina que Coca Cola posee distintos canales de distribución segmentados, es decir, que son específicos o adaptados de acuerdo a las características del entorno y los clientes; y que, la importancia de los canales de distribución se basa en la eficiencia de la entrega oportuna de sus productos al consumidor final, con base en una planificación estratégica de las ventas y su proceso de distribución (entrega, transporte y almacenamiento), a razón de que esto propicia la optimización de recursos e incide directamente sobre el nivel de ingresos. Por ello se concluye que el éxito de Coca Cola radica en gran medida en su estrategia de distribución y ventas.
Keywords: CANALES DE DISTRIBUCIÓN; COCA COLA; EMPRESA; VENTAS; PLANIFICACIÓN; CONSUMIDOR FINAL